Continuous training of the teacher-educator: constitution of the professional knowledge in collective reflective processes - Lauxen, Ademar Antonio; Del Pino, José Claudio (Revista Eletrônica de Educação, 2017)
The objective of the research that motivated this article is to discuss the knowledge that characterize the teacher as well as the attributes related to teacher-educator and its relevance to the constitution of critical and reflective professional. This is a qualitative character study, in the perspective of investigation-action, resulting from interviews with semi-structured questions, conducted with ten teachers-educators, acting in the chemistry teaching degree course. The research reveals attributes and characteristics inherent in a good teacher and which associate with the teacher-educator, discussing how the interviewed correlate those two categories. Besides, it points to the necessity of reflective processes by the educator, signaling to this reflection to be able to break with the purely individual process and constitute in a collective social practice in intra-institutional space/time. The data also reveal that the teachers-educators have points of convergence with knowledge for teaching, and that those to be revealed and problematized in spaces/times the continuous training can contribute to a better understanding of the teacher’s being and doing. Keywords: Teacher-educator, Teaching knowledge, Reflexive researcher. References: BOGDAN, R.; BIKLEN, S. K. Investigação qualitativa em educação: uma introdução à teoria e aos métodos. Porto: Porto Editora, 2010. CACHAPUZ, A. et al. (Org.). A necessária renovação de ensino das ciências. São Paulo: Cortez, 2005. CÂNDIDO, C. M. et al. A representação social do “bom professor” no ensino superior. Psicologia & Sociedade, Porto Alegre, v 26, n. 2, 2014. p. 356-365. CAVACO, M. H. Ofício de professor: o tempo e as mudanças. In: NÖVOA, A. (Org.). Profissão professor. Porto: Porto Editora, 1999. p. 155-191. CUNHA, M. I. de. O bom professor e sua prática. 24ª. ed. Campinas, SP: Papirus, 2012. DEL PINO, J. C. Um estudo sobre a organização curricular de disciplinas de química geral. Acta Scientiae. Canoas-RS, v. 14, n. 1, p. 94-114, jan./abr. 2012. FEITOZA, L. A. et al. Representação do bom professor na perspectiva dos alunos de arquivologia. Perspectiva em Ciência da Informação. Belo Horizonte, v. 12, n.2, p. 158-167, maio/ago 2007. FIORENTINI, D. et al. Saberes docentes: um desafio para acadêmicos e práticos. In: GERALDI, C. M. G.; FIORENTINI, D.; PEREIRA, E. M. de A. (Org.). Cartografia do trabalho docente: professor(a)-pesquisador(a). 2. Ed. Campinas, SP: Mercado de Letras. 2011, p. 307- 335. GALIAZZI, M. do C. Educar pela pesquisa: ambiente de formação de professores de ciências. Ijuí: Unijuí, 2011. GAUTHIER, C. et al. Por uma teoria da pedagogia: pesquisas contemporâneas sobre o saber docente. 3ª. ed. Ijuí: Unijuí, 2013. GHEDIN, E. et al. Estágio com pesquisa. São Paulo: Cortez, 2015. GRILLO, M. Percursos da constituição da docência. In: ENRICONE, D. (Org.). A docência na educação superior: sete olhares. 2ª. ed. Porto Alegre: EDIPUCRS, 2008. p. 65-79. LÜDKE, M.; ANDRÉ, M. E. D. A. de. Pesquisa em educação: abordagens qualitativas. 2ª. ed. Rio de Janeiro: EPU, 2013. MARQUES, M. O. Educação/interlocução, aprendizagem/reconstrução de saberes. Ijuí: Unijuí, 1996. MALDANER, O. A. A formação inicial e continuada de professores de química professor/pesquisador. 4ª. ed. Ed. Ijuí: Unijuí, 2013. MORAES, R.; GALIAZZI, M. do C. Análise textual discursiva. 2ª. ed. rev. Ijuí: Unijuí, 2011. NERY, B. K.; MALDANER, O. A. (Org.). Formação de professores: compreensões em novos programas e ações. Ijuí: Unijuí, 2014. NÓVOA, A. Formação de professores e profissão docente. In. NÓVOA, A. (Coord). Os professores e a sua formação. 2ª. ed. Lisboa: Dom Quixote, 1995. p. 15-33. NUNES, A. K.; HELFER, C. L. de L. Diagnóstico do desempenho na docência da graduação da UNISC. Avaliação, Campinas/Sorocaba-SP, v. 14, n. 1, p. 169-183, mar. 2009. PACHANE, G. G. Quem é seu melhor professor universitário e por quê? Características do bom professor universitário sob o olhar de licenciandos. Educação. v. 37, n. 2. p. 307-320, maio/ago. 2012. Santa Maria-RS, 2012. PÉREZ GÓMEZ, A. O pensamento prático do professor: a formação do professor como profissional reflexivo. In: NÓVOA, A. (Coord.). Os professores e a sua formação. 2ª. ed. Lisboa: Dom Quixote, 1995. p. 93-114. QUADROS, A. L.; MORTIMER, E. F. Formadores de professores: análise de estratégia que os tornam bem sucedidos junto aos estudantes. Revista Investigação em Ensino de Ciências. v. 21, n. 1, p. 12-30, mar. 2016. SCHÖN, D. A. Formar professores como profissionais reflexivos. In: NÓVOA, A. (Coord.). Os professores e a sua formação. 2ª. ed. Lisboa: Dom Quixote, 1995. p. 77-91. TARDIF, M.; LESSARD, C. O trabalho docente: elementos para uma teoria da docência como profissão de interações humanas. 8ª. ed. Petrópolis, RJ: Vozes, 2013. TARDIF, M. Saberes docentes e formação profissional. 17ª. ed. Petrópolis, RJ: Vozes, 2014. VENTURA, M. C. A. A. et al. O “bom professor” – opinião dos estudantes. Revista de Enfermagem Referência, III série, n. 5, p. 95-102, dez 2011. YIN, R. K. Estudo de caso: planejamento e métodos. 2ª. ed. Porto Alegre: Bookmam, 2001. ZANON, L. B. et al. Articulações entre desenvolvimento curricular e formação inicial de professores de Química. In: ECHEVERRÍA, A. R.; ZANON, L. B. (Org.). Formação superior em química no Brasil: práticas e fundamentos curriculares. 2ª. ed. Ijuí: Unijuí, 2016. p. 208-231. ZEICHNER, K. M. A formação reflexiva de professores: idéias e práticas. Lisboa: EDUCA, 1993. ZEICHNER, K. M. Novos caminhos para o practicum: uma perspectiva para os anos 90. In: NÓVOA, A. (Coord.). Os professores e a sua formação. Lisboa: Dom Quixote, 1995. p. 115-138.